Modeling a screw extruder for FFF 3D printing - Razumov-Fryziuk, I.A.; Gurin, D.V.; Nikitin, D.O.; Strilets, R.Ye.; Blyzniuk, D.S. (Radiotekhnika, 2022)
The article presents the development and modeling of a screw extruder for 3D printers operating on the FFF technology, namely, the Fused Filament Fabrication (“production by fusing threads”). Extruders, usually installed on FFF 3D printers, use a thermoplastic polymer filament as a material. There are two filament standards: 1.75mm and 2.85mm. The minimum cost of such a filament starts from 11 per kilogram (ABS plastic 1.75 mm). The cost of more expensive filaments can reach several thousand or even tens of thousands per kilogram (depending on the material, filler, the presence of inhibitors, dyes, etc.). The cost of the material is much higher than granulated primary plastics and even more so recycled materials. In addition, the extruder nozzle diameter is typically limited to 1.2mm for 1.75mm filament. Thus, when printing large products, for which the detail and roughness of vertical surfaces are not so important, increase in the diameter of the extruder nozzle will increase significantly the printing speed due to the increase in the thickness of the print layer and the width of the print line. To produce filament, screw filament extruders are used, which work on the principle of injection molding machines. The authors propose a calculation of the parameters of a screw extruder for an FFF 3D printer, which will directly use granulated primary plastics or crushed plastic recyclables as a material. The use of a screw extruder will reduce the cost of the printed product and increase significantly the diameter of the extruder nozzle, which will significantly reduce the production time for large-sized products. When designing a screw extruder, it is necessary to adhere to two main strategies: minimizing the weight and size parameters of the extruder and ensuring the required linear productivity. On the one hand, the extruder must be as light as possible to be able to increase the printing speed, on the other hand, it must provide the necessary linear performance to be able to extrude plastic at printing speeds. Modeling is made for nozzles with a diameter of 1mm and 5mm. According to the calculation results, the screw extruder has a 3-fold and 37-fold margin of linear productivity, respectively.